2020
DOI: 10.1016/j.foodres.2020.109810
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the variability in physical, cooking, and nutritional properties of Zamnè, a wild food in Burkina Faso

Abstract: Highlights The wild crop Zamnè exhibited characteristics of dry and hard-to-cook legume. The physical, cooking, and nutritional properties of Zamnè showed low variability. It was confirmed that there is a potential mix-up of Zamnè and pseudoZamnès . The traditional cooking of Zamnè … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 28 publications
2
37
1
Order By: Relevance
“…Accordingly, the non-proteinogenic amino acids reported from Senegalia seeds are discussed in section 5.6. Besides, Guissou et al (2017) have reported a large discrepancy between the sum of 17 proteinogenic amino acids' content (7.8 g/100 g dm) and crude protein content (35-40 g/100 g dm) (Drabo et al, 2020;Hama-Bâ et al, 2017;Msika et al, 2017) from S. macrostachya seeds, suggesting a high content of non-protein nitrogen. The amount of data is very limited and inconsistent, making it difficult to conclude the nutritional property of Senegalia seed proteins.…”
Section: Protein Nutritional Quality and Functional Propertiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Accordingly, the non-proteinogenic amino acids reported from Senegalia seeds are discussed in section 5.6. Besides, Guissou et al (2017) have reported a large discrepancy between the sum of 17 proteinogenic amino acids' content (7.8 g/100 g dm) and crude protein content (35-40 g/100 g dm) (Drabo et al, 2020;Hama-Bâ et al, 2017;Msika et al, 2017) from S. macrostachya seeds, suggesting a high content of non-protein nitrogen. The amount of data is very limited and inconsistent, making it difficult to conclude the nutritional property of Senegalia seed proteins.…”
Section: Protein Nutritional Quality and Functional Propertiesmentioning
confidence: 97%
“…Carbohydrates are the principal constituent of Senegalia seeds and evoke high proportions of free sugars (6.8-7.2 g/100 g dm), dietary fibers (16-38 g/100 g dm), and bioactive polysaccharides (Drabo et al, 2020;Mersha et al, 2017;Msika et al, 2017;Yadav & Bharadwaj, 1971;Zongo et al, 2022). Notwithstanding the high dietary fiber contents of Senegalia seeds, their compositions remain poorly investigated.…”
Section: Carbohydrate Compositions and Dietary Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…The true density of the pomace ranged from 1112.10 kg m −3 to 1674.12 kg m −3 . Then pomace porosity was calculated by knowing densities (Drabo et al, 2020; Li et al, 2021). Final pomace porosity was in the range of 12.38% to 23.44%.…”
Section: Discussionmentioning
confidence: 99%